MANAGING OF INDUSTRIAL FISHING IN THE DISPUTED AREA OF THE ARCTIC REGION: PROBLEMS AND SOLUTIONS - N. Tropnikova (Вестник университета)
The article substantiates the need for management of industrial fisheries in the disputed areas of the Arctic on the basis of its own national interests and compromise. Examines the solution of some problems in the field of fisheries management on the basis of Russian-Norwegian cooperation.